NOVA FOOD ACQUISITION AND CONSUMPTION AMONG RURAL AND URBAN HOUSEHOLDS IN SOUTH AFRICA AND GHANA - Nana Ama Frimpomaa Agyapong; Reginald Adjetey Annan; Florian Kroll; Charles Apprey; Linda Nana Esi Aduku; Robert Aidoo; Elizabeth Catherina Swart
ABSTRACT Objective: This study aims to determine differences in food consumption by the NOVA food categories in South Africa and Ghana and how they relate to poverty and food supply systems. Design: This study used a cross-sectional design to assess household food acquisition and lived poverty index. Setting: The study was conducted in Khayelitsha and Mount Frere, urban and rural communities in South Africa, respectively, and Ahodwo and Ejuratia, urban and rural communities in Ghana, respectively. Participant: An adult in charge of or knowledgeable about household food acquisition and consumption was selected to participate in the study. Results: A total of 1299 households participated in the study. Supermarkets were a prominent source of ultra-processed foods for households in South Africa, while informal outlets were an important source of ultra-processed foods in Ghana. Consumption of unprocessed foods was higher among South African households (58.2%) than Ghanaian households (41.8%). In South Africa, deprivation was associated with increased odds of infrequent consumption of both unprocessed foods (OR 3.431 p<0.001) and ultra-processed foods (OR 2.656 p<0.001) compared to non-deprivation. In Ghana, no significant associations were observed between household deprivation and consumption of the NOVA food classes. Conclusion: Different food supply systems and poverty are associated with household acquisition of the different NOVA food classes. Policies should be geared towards formal shops in South Africa and informal shops in Ghana to reduce the consumption of key obesogenic foods.